Place of Transport in the Sales Policy of the Industrial Enterprise - Hodoskina, O. A.; Moiseienkova, O. Y. (Science and Transport Progress, 2021)
Purpose. Currently, the organization of sales at the enterprise is the main and continuous process that provides the enterprise with its economic efficiency and bringing the goods to the consumer. The purpose of this work is to analyze and compare modes of transport and its role in the marketing of products by an enterprise. Methodology. To build a model for the marketing activity of an enterprise, as well as when modeling the mechanism of functioning of its organizational, economic and production structure and the place of transport in the structure of an industrial enterprise, elements of economic and mathematical modeling were used. Analysis of the data obtained allows you to choose the best method of transportation, which is extremely important to ensure that the needs of the enterprise, as well as the needs of consumers, are met. Findings. Marketing and logistics services of the enterprise need, having studied all the advantages and disadvantages of all types of transport, to choose the most optimal mode of transport when transporting goods. For the sale of its products, the enterprise should take into account that over time, the costs of different types of transport may change, and the transportation schemes should be revised. The paper compares the modes of transport and the structure of freight turnover by mode of transport (as a percentage of the total). Originality. The use of a mathematical apparatus in the construction of functional dependencies that make up a general economic and mathematical model that characterizes the organization of the marketing activities of an enterprise will allow not only to identify «weak» points, but also to adjust the marketing policy of the enterprise accordingly, relying not on abstract conclusions, but on the obtained clear dependencies. Practical value. The result is, first of all, a reduction in costs in the marketing policy of the enterprise and an increase in competitiveness, an increase in profits and maximum satisfaction of consumer requirements.